Immune-related SERPINA3 as a biomarker involved in diabetic nephropathy renal tubular injury - Fan, Zuyan; Gao, Yan; Jiang, Nan; Zhang, Fengxia; Liu, Shuangxin; Li, Quhuan (Frontiers in Immunology, 2022)
Diabetic nephropathy (DN) is the leading cause of end-stage renal disease and has become a serious medical issue globally. Although it is known to be associated with glomerular injury, tubular injury has been found to participate in DN in recent years. However, mechanisms of diabetic renal tubular injury remain unclear. Here, we investigated the differentially expressed genes in the renal tubules of patients with DN by analyzing three RNA-seq datasets downloaded from the Gene Expression Omnibus database. Gene set enrichment analysis and weighted gene co-expression network analysis showed that DN is highly correlated with the immune system. The immune-related gene SERPINA3 was screened out with lasso regression and Kaplan–Meier survival analyses. Considering that SERPINA3 is an inhibitor of mast cell chymase, we examined the expression level of SERPINA3 and chymase in human renal tubular biopsies and found that SERPINA3 was upregulated in DN tubules, which is consistent with the results of the differential expression analysis. Besides, the infiltration and degranulation rates of mast cells are augmented in DN. By summarizing the biological function of SERPINA3, chymase, and mast cells in DN based on our results and those of previous studies, we speculated that SERPINA3 is a protective immune-related molecule that prevents renal tubular injury by inhibiting the proliferation and activation of mast cells and downregulating the activity of chymase.